Ephedra alata Subsp. Alenda as a Novel Source of Bioactive Phytochemicals: Characterization Based on the Mass Spectrometry and Profiling of Antioxidant and Anti-Inflammatory Properties - Afoua Mufti; María del Mar Contreras; Irene Gómez-Cruz; Abdullah Alshamrani; Saber Nahdi; Lamjed Mansour; Salah Alwasel; Abdel Halim Harrath; Nizar Tlili (Life, 2023)
The aim of the present study was to examine, for the first time, the phytochemical content of Ephedra alata pulp extract (EAP) and explore its antioxidant and anti-inflammatory capacities. High-performance liquid chromatography-electrospray ionization-quadrupole-time-of-flight mass spectrometry (HPLC–ESI–QTOF/MS) was used for phytochemical analysis and three in vitro antioxidant assays together with three in vitro anti-inflammatory tests were used for the assessment of biological activity. The HPLC–ESI–QTOF/MS analysis revealed the presence of 42 metabolites, including flavonoids, sphingolipides, fatty acids, ephedrine derivatives, and amino acid derivatives. In vitro findings revealed that EAP has interesting 2,2-diphenyl-1-picrylhydrazyl (DPPH), superoxide, and ferrous ion chelating capacities (IC50 values were 0.57 mg/mL, 0.55 mg/mL, and 0.51 mg/mL for DPPH, superoxide radical, and ferrous ion, respectively). Furthermore, EAP showed a noticeable anti-inflammatory ability by inhibiting the two cyclooxygenase isoforms, COX-1 and COX-2 (IC50 of 59.1 and 58.8 µg/mL for COX-1 and COX-2, respectively), preventing protein denaturation (IC50 = 0.51 mg/mL), and protecting membrane stabilization (IC50 = 0.53 mg/mL). The results highlighted the use of Ephedra alata pulp as a potential source of natural compounds with therapeutic effects for the management of inflammatory disorders.